Haemolymph proteins of the Indian white shrimp, Penaeus indicus (H. Milne Edwards) - Laxmilatha, P; Laxminarayana, A (Indian Journal of Fisheries, 2011)
Haemolymph proteins of the Indian white shrimp, Penaeus indicus were characterised by Sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDSPAGE). The most important fractions were the cuproproteins-hemocyanins, characterized by two fractions. The two fractions are also lipo- and glyco-proteic in nature. Males and females possess similar protein pattern and the maximal number of fractions separated was 16.